Role of Micro-And Macro-Nutrients in Obesity Onset - Andrea MP Romani (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2016)
The incidence of obesity has been increasing exponentially for the last 30 years, and it is posing a major health issue in the US and worldwide. The 2015 reports by the World Health Organization (WHO) and the Center for Disease Control (CDC) in the US indicate that approximately 1.9 billion people worldwide are overweight and more than 600 million are frankly obese, irrespective of genders, races, ethnicities, ages, and socio-economic strata [1]. As individuals become obese or overweight at a younger age, the incidence and severity of obesity-related long-term complications has also increased significantly. Type 2-diabetes, particular forms of cancer (i.e. breast, ovarian, colon, and liver cancer), and cardiovascular diseases including hypertension and stroke represent the most common complications of obesity, and all carry expensive price-tags. In the particular case of diabetes, previous predictions estimating ~28 million people in the US to be affected by diabetes by the year 2030 have proven to be optimistic as 29.1 million individuals were reported to be diabetic by the year 2012, with an attached price-tag for the US healthcare system in excess of 250 billion USD between direct and indirect costs including lost productivity [2].